Small Antenna Based on MEMS and Metamaterial Properties for Reconfigurable Applications - G. Rosas-Guevara; R. Murphy-Arteaga; W. Moreno (International Journal of Antennas and Propagation)
This paper presents the design of a novel, small coplanar antenna using microelectromechanical systems (MEMS) and metamaterial (MTM) properties. The antenna is designed using coplanar waveguide (CPW) technology, presenting lower dielectric losses and higher signal integrity. The design method for this MEMS-MTM antenna, herein presented, is based on a composite right/left hand (CRLH) transmission Line (TL) using a mixed approach; considering the circuit model and full-wave simulations. The fabrication process is based on high-resistivity silicon wafers. The radiator has dimensions of 0.017 λg × 0.033 λg and a thickness of 0.0116 λg, whereas the complete circuit, of 5 mm × 11 mm, is equivalent to 0.14 λg × 0.31 λg. The antenna is designed using MEMS parallel-plate capacitors as the radiator, which also allows for the reconfiguration of the central frequency by electrostatically varying the capacitance. The results presented here correspond to a central frequency of 8.4 GHz. Due to its small size, this antenna has a wide variety of applications in wireless circuits for different fields.